2016
DOI: 10.1089/jop.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in the Trabecular Meshwork for Regulating Intraocular Pressure

Abstract: Intraocular pressure (IOP) is still the main treatment target for glaucoma. Outflow resistance mainly exists at the trabecular meshwork (TM) outflow pathway, which is responsible for IOP regulation. Changes of TM cellularity and TM extracellular matrix turnover may play important roles in IOP regulation. In this article, we review basic anatomy and physiology of the outflow pathway and TM stem cell characteristics regarding the location, isolation, identification and function. TM stem cells are localized at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 62 publications
1
45
1
Order By: Relevance
“…The candidate TM marker AQP1 was preferentially expressed in these non-filtering TM cells, consistent with the observation that deletion of AQP1 in mice did not affect outflow facility (Figure 3J) (Zhang et al, 2002). Although it has been suggested that Schwalbe's line contains TM precursors (Kelley et al, 2009), we detected no DE genes suggestive of "stemness" (Yun et al, 2016) in this cluster; if present, they may have been too rare to be detected.…”
Section: Introductionsupporting
confidence: 88%
“…The candidate TM marker AQP1 was preferentially expressed in these non-filtering TM cells, consistent with the observation that deletion of AQP1 in mice did not affect outflow facility (Figure 3J) (Zhang et al, 2002). Although it has been suggested that Schwalbe's line contains TM precursors (Kelley et al, 2009), we detected no DE genes suggestive of "stemness" (Yun et al, 2016) in this cluster; if present, they may have been too rare to be detected.…”
Section: Introductionsupporting
confidence: 88%
“…It has been reported that there are tissue‐specific stem cells in the TM 26‐30 . Several groups have successfully isolated and characterized human TM stem cells 31‐33 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested not only low TM cellularity (Alvarado, Murphy & Juster, 1984;Baleriola et al, 2008), but also TM cytoskeleton and phagocytosis changes in primary open angle glaucoma (Clark et al, 1995;Fatma et al, 2009;Izzotti et al, 2010;Saccà, Pulliero & Izzotti, 2015;Peters et al, 2015;Micera et al, 2016). Repopulating diseased TM with fresh, functional TM cells has been shown to restore homeostasis of normal outflow and thus might represent a novel therapeutic breakthrough (Du et al, 2013;Abu-Hassan et al, 2015;Yun et al, 2016;Zhu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%